Astrocyte Responses Influence Local Effects of Whole‐Brain Magnetic Stimulation in Parkinsonian Rats - Natale, Giuseppina; Colella, Micol; De Carluccio, Maria; Lelli, Daniele; Paffi, Alessandra; Carducci, Filippo; Apollonio, Francesca; Palacios, Daniela; Viscomi, Maria Teresa; Liberti, Micaela; Ghiglieri, Veronica (Movement disorders, 2023)
Background Excessive glutamatergic transmission in the striatum is implicated in Parkinson's disease (PD) progression. Astrocytes maintain glutamate homeostasis, protecting from excitotoxicity through the glutamate–aspartate transporter (GLAST), whose alterations have been reported in PD. Noninvasive brain stimulation using intermittent theta‐burst stimulation (iTBS) acts on striatal neurons and glia, inducing neuromodulatory effects and functional recovery in experimental parkinsonism. Objective Because PD is associated with altered astrocyte function, we hypothesized that acute iTBS, known to rescue striatal glutamatergic transmission, exerts regional‐ and cell‐specific effects through modulation of glial functions. Methods 6‐Hydroxydopamine‐lesioned rats were exposed to acute iTBS, and the areas predicted to be more responsive by a biophysical, hyper‐realistic computational model that faithfully reconstructs the experimental setting were analyzed. The effects of iTBS on glial cells and motor behavior were evaluated by molecular and morphological analyses, and CatWalk and Stepping test, respectively. Results As predicted by the model, the hippocampus, cerebellum, and striatum displayed a marked c‐FOS activation after iTBS, with the striatum showing specific morphological and molecular changes in the astrocytes, decreased phospho‐CREB levels, and recovery of GLAST. Striatal‐dependent motor performances were also significantly improved. Conclusion These data uncover an unknown iTBS effect on astrocytes, advancing the understanding of the complex mechanisms involved in TMS‐mediated functional recovery. Data on numerical dosimetry, obtained with a degree of anatomical details never before considered and validated by the biological findings, provide a framework to predict the electric‐field induced in different specific brain areas and associate it with functional and molecular changes. © 2023 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.